2011
DOI: 10.4100/jhse.2011.63.05
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of marathon performance time on the basis of training indices

Abstract: Tanda G. Prediction of marathon performance time on the basis of training indices. J. Hum. Sport Exerc. Vol. 6, No. 3, pp. 511-520, 2011. The purpose of this study was to examine the relationship between marathon performance time (MPT) and some training factors recorded for a given number of weeks prior to a race. Twenty-two runners, age 28-54 years, participated as subjects in this investigation. They kept daily exercise records during their marathon training for an overall number of 46 races, whose marathon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 19 publications
2
47
1
Order By: Relevance
“…In contrast with the findings of Tanda, we could not confirm the findings describing an equation based on training duration and training speed 25. The differences between the results reported by Tanda and our findings may be partly explained by the longer period of the training diary used in our study, the difference in weekly running kilometers, greater variability in marathon race time, and the larger sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with the findings of Tanda, we could not confirm the findings describing an equation based on training duration and training speed 25. The differences between the results reported by Tanda and our findings may be partly explained by the longer period of the training diary used in our study, the difference in weekly running kilometers, greater variability in marathon race time, and the larger sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Frequency, intensity, and volume of training seem to be of great importance 10,11,13,20. Tanda described a strong correlation between training volume and intensity during an eight-week training period and marathon performance 25. Different training variables, such as the number of training units, kilometers completed during a training unit, maximum kilometers completed during a training unit, total time spent running during training, mean weekly running kilometers, maximal weekly running kilometers, and mean daily run kilometers were related to marathon race times 11,20,26.…”
Section: Introductionmentioning
confidence: 99%
“…The authors chose the measurement time running per week based on this principle and did not record participants distance run per week. Tanda et al and Hagan et al found distance run per week recorded in a training diary predictive of MPT (4,8). The recording of the number of hours run per week by participants in this study was subject to recall bias as it was asked retrospectively.…”
Section: Discussionmentioning
confidence: 91%
“…Tanda (8) explored training factors in a small study of 22 runners. They found a significant correlation between MPT and both mean distance run per week (r = 0.81) and mean training pace (r = 0.85) (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation